EFISIENSI DAN EFETIVITAS PEMBELAJARAN DARING SISWA SMA DI KECAMATAN KEBOMAS KABUPATEN GRESIK - Rima Nurul Hidayah; Isa Anshori (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2021)
The COVID-19 pandemic is a problem that has hit most countries in the world, including Indonesia. This certainly has an impact on the life sector, especially in the field of education. The enactment of physical distancing policy requires educators to make an overhaul in the implementation of online learning. This study aims to see the efficiency and effectiveness of online learning so far. In this case the research was carried out using a qualitative research method with a phenomenological approach. The research was located in Kebomas Gresik Senior High School. The results showed that the implementation of online learning runs efficiently and effectively if: (1) Online learning facilities are adequate (2) The preparation of teachers and students is maximum (3) Teaching and learning activities run effectively. These three things are mutually sustainable to realize the effectiveness of online learning during the current COVID-19 pandemic.